Review of the Representation of History in the New Media - Abdul Karim Zamri, Norena (School of Social Sciences, 2015)
History is often taught through textbooks. This consideration is intended to ensure that people respect leader and community contribution to maintain and develop excellences of civilization. However, few historians have considered in depth impact on the ways that history is being represented and communicated in the public sphere as the new media has become increasingly pervasive in today’s life. Students of history have generally held a dim opinion of the state of knowledge on the new media, pointing to many inaccuracies written by the amateurs. The emergence of the new media has transformed the nature of the public information which enables ordinary people a greater degree of participation in the public history making. The collection examined in this review paper focuses on the ideas and issues of the representation of Malaysia’s history in the new media, as well as to point the possible future direction for research and reflection. The challenges associated with the representation of Malaysia’s history and possible solutions are discussed, including a review of the literature related to media representation.